Extending the high-order harmonic generation cutoff by means of self-phase-modulated chirped pulses. (24th October 2016) - Neyra, E; Videla, F; Pérez-Hernández, J A; Ciappina, M F; Roso, L; Torchia, G A
Abstract: In this letter we propose a complementary approach to extend the cutoff in high-order harmonic generation (HHG) spectra beyond the well established limits. Inspired by techniques normally used in the compression of ultrashort pulses and supercontinuum generation, we show this extension can be achieved by means of a nonlinear phenomenon known as self-phase-modulation (SPM). We demonstrated that relatively long optical pulses, around 100 fs full-width half maximum (FWHM), non linearly chirped by SPM, are able to produce a considerable extension in the HHG cutoff. We have also shown it is possible control this extension by setting the length of the nonlinear medium. Our study was supported by the numerical integration of the time-dependent Schrödinger equation joint with a complete classical analysis of the electron dynamic. Our approach can be considered as an alternative to the utilization of optical parametric amplification (OPA) and it can be easily implemented in usual facilities with femtosecond laser systems. This technique also preserves the harmonic yield in the zone of the plateau delimited by I p + 3.17 Up law, even when the driven pulses contain larger wavelength components.